Hubungan Antara Asupan Energi, Zat Gizi Makro dan Total Energy Expenditure dengan Status Gizi Anak Sekolah Dasar - Baiq Qamariyah; Triska Susila Nindya (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2018)
Background: Nutritional status of students can be influenced by many factors such as energy intake, macro nutrients intake and total energy expenditure.Objectives: this study aimed to determine association of energy intake, macro nutrients intake and total energy expenditure with nutritional status of elementary students.Methods: this study was observasional analitic research with cross-sectional design wich was done in SDN Pacarkembang 1 Surabaya on July 2017.The sample was 66 students in grade 4 and 5 with simple random sampling. Variabel in study was nutritional status, energy intake, macro nutrient intake, and total energy expenditure. Data were collected through interview using food recall 2 x 24 hour, physical activity recall, weight and high measurement. Analysis data used independent sample T-test analysis.Results: this study showed the most of nutritional status was normal (69.7%). There were correlations of energy intake (p=0.000), protein (p=0.017), fat (p=0.040) carbohydrate (p=0.001) and total energy expenditure (p=0.000) with nutritional status of elementary students.Conclusion: energy intake, macro nutrient intake and total energy expenditure were associated with nutritional status of school children.School children should reduce the consumption of food high in energy, protein, fat and increase physical activity.ABSTRAKLatar Belakang: Status gizi pada anak sekolah dapat dipengaruhi banyak faktor diantaranya asupan energi, asupan zat gizi makro dan total energy expenditure.Tujuan: penelitian ini adalah mempelajari hubungan antara asupan energi, zat gizi makro dan total energy expenditure dengan status gizi anak sekolah dasar.Metode: Penelitian adalah observasional analitik dengan rancang studi cross-sectional yang dilaksanakan di SDN Pacarkembang 1 Surabaya pada Juli 2017. Sampel Penelitian adalah siswa kelas 4 dan 5 sebanyak 66 orang yang diambil dengan simple random sampling. Variabel penelitian meliputi status gizi, asupan energi, asupan zat gizi makro dan total energy expenditure. Pengumpulan data menggunakan metode wawancara dengan recall 2x24 jam, recall aktivitas fisik, pengukuran berat badan dan tinggi badan. Analisis data menggunakan uji independent sampel T-test.Hasil: penelitian menunjukkan bahwa sebagian besar status gizi siswa normal (69,7%). Terdapat hubungan signifikan antara asupan energi (p=0,000), protein (0,017), lemak (p=0,040), karbohidrat (p=0,001) dan total energy expenditure (p=0,000) dengan status gizi anak sekolah dasar.Kesimpulan: asupan energi, zat gizi makro dan total energy expenditure berhubungan dengan status gizi anak sekolah dasar. Sebaiknya anak sekolah dasar dapat mengurangi konsumsi makanan tinggi energi protein dan lemak serta meningkatkan aktivitas fisik.